FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAH LAKU KEWARGANEGARAAN ORGANISASI - Zaid, Dina Syamilah; Mohamed Nasir, Nor Saidi (Jurnal ’Ulwan, 2024)
An employee who does something without coercion and voluntarily in an organization is often referred to as having organizational citizenship behavior. Organizational citizenship behavior is an important component for employees who deal directly with customers. This is because customer satisfaction in the hospitality industry depends on how employees can meet customer expectations, and this requires employees to carry out activities that are not part of their job. However, organizational commitment can also contribute to the success of an organization. At the same time, organizational commitment is also required by each employee so that they can contribute their services, efforts, and energy to the organization. This study was conducted to examine the factors that influence organizational citizenship behavior among hotel employees. In addition, the results of these results are expected to add knowledge related to the characteristics of individuals who have organizational citizenship behavior and organizational commitment. The results of this study are also expected to contribute to a deep understanding of the importance of organizational citizenship behavior and organizational commitment, which are driving forces in the effectiveness of the hospitality industry. The results of this study are expected to be a guide and refer to the parties involved in terms of the preparation of human resource management design and its content so that it is more effective, suitable, and meets the needs of the field of work. An understanding of this aspect can be used as a guide for the management of the organization involved in the challenging work environment of today.